Kedudukan Akad Digital Dalam Perspektif Hukum Ekonomi Syariah - Mardia Pulungan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid development of digital technology has significantly transformed transactional practices, including within the framework of Islamic economic law. This study aims to analyze the legal standing of digital contracts from an Islamic perspective, the challenges in their implementation, and their prospects for advancing the Islamic economy. This research employs a qualitative approach through library research with a descriptive-analytical method. The findings indicate that digital contracts are principally valid under Islamic jurisprudence as long as they fulfill the pillars and conditions of contracts while ensuring fairness, transparency, and protection of rights for all parties. Nevertheless, their implementation faces challenges such as identity authentication, data security, information transparency, and technological infrastructure readiness. The integration of Islamic law with national regulations, including the Electronic Information and Transaction Law (ITE Law), as well as regulations issued by the Financial Services Authority (OJK) and Bank Indonesia, is crucial for strengthening the legal basis of digital contracts. The prospects of digital contracts are highly promising in expanding Islamic financial inclusion and enhancing the competitiveness of the global Islamic economy. Thus, this study highlights the flexibility of Islamic law in responding to contemporary developments while contributing significantly to strengthening the Islamic economic system in the digital era.